Social Media And Social Interaction Of Urban Youth - Suhaeb, Firdaus W; Kaseng, Ernawati S (Program Studi Sosiologi, 2025)
The development of digital technology has driven massive social media penetration in the lives of adolescents, especially in urban areas. This study aims to analyze the impact of social media on adolescent social interaction patterns. The method used is a literature study from various previous sources. The results of the study show that social media has positive impacts such as expanding social networks and increasing self-expression, but also has negative impacts such as decreased face-to-face interaction, cyberbullying, and addiction. Factors such as duration of use, type of content, digital literacy, and the role of family and school greatly influence these impacts. This study recommends managing social media use wisely so that adolescent social interactions remain healthy.